Síntese de membranas condutoras superiônicas pela rota vitrocerâmica para prospecção de lítio do oceano - Antoniolli, João Felipe Pierdoná (2025)
The advancement of technologies and the increasing use of batteries in recent years have heightened the demand for lithium, with consumption projections reaching 2.4 Mton by 2030. Accordingly to current data, there is growing concern that land reserves will not suffice to meet this long-term demand, making the exploration of alternative sources essential. One such alternative is lithium extraction from seawater, in which reserves of this element exceed terrestrial reserves by nearly 2000 times. This project aims to develop membranes for lithium extraction from seawater using glass-ceramics of composition Li1.5Al0.5Ge1.5(PO4)3 (LAGP), as well as to maximize their ionic conductivity through the study of crystallization heat treatments. The synthesis began with glass preparation, involving mixing precursor powders, calcinating at 700 ° C for 2 hours, and melting at 1250 °C for 30 minutes. The glass was then crystallized in two stages: nucleation at 513°C for 1, 2, and 3 hours (N1, N2, and N3), followed by growth at 800°C for 3 and 4 hours (C3 and C4). Samples, named N1C3, N2C3, N3C3, N1C4, N2C4, and N3C4 according to the heat treatments. The average density obtained was up to 96%, with the N3C4 sample, also showing a high ionic conductivity of 4.4.10−4 S.cm−1 at room temperature. After the crystallization study, LAGP glass-ceramic membranes with a diameter of 25 mm were synthesized and tested in electrodialysis to recover lithium from concentrated solutions, achieving a high extraction rate of 13.16 g/m2h. Furthermore, lithium extraction from seawater was demonstrated, with significant sodium selectivity, reducing its concentration by 100 times, highlighting the material’s potential for lithium recovery from aqueous solutions. Additionally, it was possible to qualitatively correlate ionic selectivity with electrochemical properties such as open-circuit potential and polarization resistance.